Braun : fifty years of design and innovation. - Polster, Bernd, 1952- (Stuttgart : Axel Menges, 2009)
Braun is not merely a trademark; it stands for an allencompassing concept. For the last five decades, this concept has spawned innovative products with an unprecedented regularity that begs to be explained-especially as the era spanned by the history of Braun design is not exactly one characterized by continuity. Instead, the second half of the 20th century witnessed a dramatic change in living conditions.